Hurthle Cell Thyroid Carcinoma with Liver and Paraaortic Abdominal Nodal Metastasis: Progression on Sorafenib Therapy after Initial Disease Stabilization - Loharkar, Sarvesh; Basu, Sandip (World Journal of Nuclear Medicine, 2022)
Hurthle cell thyroid carcinoma (HCTC) demonstrates inferior prognosis compared with other types of differentiated thyroid cancer (DTC), along with radioiodine refractoriness and relatively poor 131I concentrating ability. We herein report a case of a middle-aged lady presenting with neck swelling for years, who on pre-surgery work-up was diagnosed to harbor metastatic nodal and lung lesions. Post-thyroidectomy and neck dissection, she was diagnosed with HCTC. Post-surgery, none of the lesions concentrated radioactive-iodine (RAI) sufficiently but showed FDG avid lesions as mediastinal nodes, lung nodules, solitary lytic sternal lesions, and unusual bilateral paraaortic abdominal nodes. She was put on tyrosine kinase inhibitor (sorafenib) and showed disease stabilization for the initial 3 years, but multiple toxicity symptoms while on sorafenib therapy that needed multiple dose adjustments. Over the period of the subsequent year, she developed significant disease progression with liver involvement. She was shifted to lenvatinib, which she tolerated well. The functional imaging profile with unusual metastatic sites, the aggressive clinical presentation and disease course of RAI refractory HCTC over 4 years on tyrosine kinase inhibitor therapy, and the role of molecular FDG-PET/CT imaging in disease monitoring and clinical management of such case is presented.
Keywords: Hurthle cell thyroid carcinoma; 18F-FDG-PET/CT; tyrosine kinase inhibitors; para-arotic lymphadenopathy; sorafenib; lenvatinib; radioiodine-refractory